Apoptosis-associated speck-like protein containing a CARD-mediated release of matrix metalloproteinase 10 stimulates a change in microglia phenotype - Sánchez, Kathryn E.; Bhaskar, Kiran; Rosenberg, Gary A. (Frontiers in Molecular Neuroscience, 2022)
Inflammation contributes to amyloid-β and tau pathology in Alzheimer’s disease (AD). Microglia facilitate an altered immune response that includes microgliosis, upregulation of inflammasome proteins, and elevation of matrix-metalloproteinases (MMPs). Studies of cerebrospinal fluid (CSF) and blood in dementia patients show upregulation of two potential biomarkers of inflammation at the cellular level, MMP10 and apoptosis-associated speck-like protein (ASC). However, little is known about their relationship in the context of brain inflammation. Therefore, we stimulated microglia cultures with purified insoluble ASC speck aggregates and MMP10 to elucidate their role. We found that ASC specks altered microglia shape and stimulated the release of MMP3 and MMP10. Furthermore, MMP10 stimulated microglia released additional MMP10 along with the inflammatory cytokines, tumor-necrosis factor-alpha (TNF alpha, Interleukin 6 (IL-6), and CXCL1 CXC motif chemokine ligand 1 (CXCL1). A broad-spectrum MMP inhibitor, GM6001, prevented TNF alpha release. With these results, we conclude that MMP10 and ASC specks act on microglial cells to propagate inflammation.